Regional Differences in Mucociliary Clearance in the Upper and Lower Airways - Rogers, Troy D.; Button, Brian; Kelada, Samir N. P.; Ostrowski, Lawrence E.; Livraghi-Butrico, Alessandra; Gutay, Mark I.; Esther, Charles R.; Grubb, Barbara R. (Frontiers in Physiology, 2022)
As the nasal cavity is the portal of entry for inspired air in mammals, this region is exposed to the highest concentration of inhaled particulate matter and pathogens, which must be removed to keep the lower airways sterile. Thus, one might expect more vigorous removal of these substances via mucociliary clearance (MCC) in this region. We have investigated the rate of MCC in the murine nasal cavity compared to the more distal airways (trachea). The rate of MCC in the nasal cavity (posterior nasopharynx, PNP) was 3-4x greater than on the tracheal wall. This appeared to be due to abundant populations of ciliated cells in the nasal cavity ( 80%) compared to the sparsely ciliated trachea ( 40%). The tracheal ventral wall exhibited a significantly lower rate of MCC than the tracheal posterior membrane. The trachealis muscle underlying the ciliated epithelium on the posterior membrane appeared to control the surface architecture and likely in part the rate of MCC in this tracheal region. In one of our mouse models (Bpifb1 KO) exhibiting a 3-fold increase in Muc5B protein in lavage fluid, MCC particle transport on the tracheal walls was severely compromised, yet normal MCC occurred on the tracheal posterior membrane. While a blanket of mucus covered the surface of both the PNP and trachea, this mucus blanket MCC transport occurred only in the PNP. In contrast, particles appeared to be transported as discrete patches or streams of mucus in the trachea. Additionally, particle transport in the PNP was fairly linear, while particle transport in the trachea often followed a non-linear route. The thick, viscoelastic mucus blanket that covered the PNP, exhibiting 10-fold greater mucus mass than the blanket covering the trachea surface, could be transported over large areas completely devoid of cells (made by a breach in the epithelial layer). In contrast, particles could not be transported over even a small epithelial breach in the trachea. The thick mucus blanket in the PNP likely aids in particle transport over the non-ciliated olfactory cells in the nasal cavity and likely contributes to humidification and more efficient particle trapping in this upper airway region.